A Study on Increasing of Heat Flux for Heat Sink in VRF Outdoor Inverter Board - Hoai-An Le,; Minh-Hung Doan, (Journal of Technical Education Science, 2025)
Increasing of heat flux for heat sink in VRF outdoor inverter board helps to increase heat sink performance, prevent over heat error caused by inverter board. For these reasons, the heat sinks are carried out to experimentally study, propose an R22 air conditioner model with the heat sinks in conditions of different hydraulic diameter (Dh), copper tube quantity (n). Three samples are same length L (150 mm), W (140 mm), HS1 sample has Dh (10.7 mm), n (1 tube); HS2 sample has Dh (4.35 mm), n (6 tubes); HS3 sample has Dh (2.98mm), n (9 tubes). While increasing resistor capacity from 100 W to 450 W, the surface temperature (chip) increases from 65°C to 105°C, leads the temperature difference of refrigerant fluid also increases. While the chip temperature obtains 105 °C, the maximum temperature difference of refrigerant fluid of HS2 (4.9°C) is higher 6.5%, 19.5% if compared to HS1 (4.6°C), HS2 (4.1°C), respectively. Besides, while increasing resistor capacity, heat flux increases. At 400 W, heat flux of HS1, HS2, HS3 obtains 20047 W/m2, 19294 W/m2, 17712 W/m2, respectively. Results show the heat flux of HS2 is respectively higher 4%, 13% if compared to HS1, HS3. Result shows that heat transfer coefficient of HS2 is higher 7%, 18% if compared to HS1, HS3. The results show that increasing of heat exchanger performance. It can be completely applied to VRF outdoor system to help to reduce over heat error in VRF outdoor inverter board. This study will serve as the basis of increasing of heat flux and is the foundation for improving heat sinks.